Microplankton biomass collected during RV SONNE cruise SO285 to the Benguela Upwelling System - Martin, Bettina; Koppelmann, Rolf (PANGAEA, 2022)
Biomass of two seize fractions of microplankton was measured of samples taken during cruise SO2853 in September/October 2021 using a Multinet Midi (55 µm mesh size, 5 depths). The sampling took place in the northern and southern Benguela upwelling system in the context of the project TRAFFIC (Trophic TRAnsfer eFFICiency in the Benguela Current). TRAFFIC aims to enlighten the energy transfer through the food webs of the northern and southern subsystems of the Benguela upwelling system.
Keywords: Benguela Upwelling System; Biomass; Microplankton